THE CONCEPT OF INCREASING ISLAMIC FINANCIAL LITERACY THROUGH EDUWISATA AS A STRATEGY FOR DEVELOPING ISLAMIC BANKING IN INDONESIA : KONSEP PENINGKATAN LITERASI KEUANGAN SYARIAH MELALUI EDUWISATA SEBAGAI STRATEGI PENGEMBANGAN PERBANKAN SYARIAH DI INDONESIA - Uyun, Siti Eniyatul (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
Supporting the creation of a maximum syariah banking system, one of which is through the level of financial literacy sayriah Indonesian people. Steps in optimizing the potential of banking development sayriah is to provide public education about Islamic financial literacy This article contains about the influence of islamic financial literacy levels in the development of Islamic banking in Indonesia, one of the factors slowing down the development of sayriah banking in Indonesia is the lack of islamic financial literacy level indonesiian society. The Financial Services Authority seeks several ways in improving financial literacy such as by providing modules and application services but it has not been able to answer the problem because the reading interest of indonesian people is very low, from here the author proposes a concept of improving the quality of Islamic financial literacy through eduwisata, a form of tourism by priority of education elements, from usula this program is expected to be able to answer one of the problems of the lack of sharia literacy levels in Indonesia where the majority of the societies who like to travel. In the study of this article using descriptive qualitative research method with the type of literature study or literature study. The discussion in writing this scientific article focuses on the concept of improving financial literacy through edutourism as a strategy for the development of sayraiah banking in Indonesia.